A Legal Protection Model Based on Local Wisdom and Islamic Principles for the Social Sustainability of Small-Scale Oil Palm Farmers in East Kalimantan - Aullia Vivi Yulianingrum; Yuli Setiyowati; Haniff Ahamat; Insan Tajali Nur (Lembaga Bale Literasi, 2026)
This study aims to formulate a model of legal protection based on local wisdom that is capable of safeguarding the social sustainability of small-scale oil palm farmers in East Kalimantan Province. This research is based on the reality that small-scale oil palm farmers frequently face legal uncertainty, economic inequality and the marginalisation of local wisdom values due to the expansion of the plantation industry. Therefore, a legal framework is required that is not only grounded in formal regulations but also accommodates local cultural values and Islamic principles. The method employed is sociological legal research using an interdisciplinary approach. Primary data was obtained through interviews with small-scale farmers, traditional leaders, religious figures and village officials in Paser Regency and Kutai Kartanegara Regency. Secondary data was gathered from legislation, academic literature, as well as fatwas and principles of Sharia. The analysis was conducted by integrating development law theory, justice theory, concepts of local wisdom and Islamic principles that emphasise the values of maslahah (public interest), ‘adl (justice) and hifz al-bi’ah (environmental protection). The research findings indicate that legal protection for small-scale oil palm farmers remains weak because existing regulations have not accommodated the social sustainability of small-scale farmers due to the dominance of an industrial paradigm in plantation management. An integrative legal protection model combining positive law, local wisdom, and the principles of Maqasid Shari’ah is proposed as an alternative to achieve substantive justice, social sustainability and environmental protection, is illustrated through the “Tali Bapintan Adat Paser” model a form of preventive legal protection comprising three main elements: land restitution based on customary consultation (mufakat adat), a social safety net (through corporate zakat (qardhul hasan), and the application of Shari’ah contracts such as musaqah.